Effects of pulling speed on structural performance of L-shaped pultruded profiles. (1st January 2021) - Vedernikov, Alexander; Tucci, Fausto; Carlone, Pierpaolo; Gusev, Sergey; Konev, Stepan; Firsov, Denis; Akhatov, Iskander; Safonov, Alexander
Abstract: Pultrusion is a highly automated process for manufacturing structural composite elements, wherein the production rate depends on the pulling speed. This study analyzed the influence of pulling speed on the structural characteristics of pultruded glass fiber/epoxy-vinyl resin 75 × 75 × 6 mm L-shaped profiles. The profiles were pultruded at three pulling speeds: 200, 400, and 600 mm/min. After fabrication, the spring-in values of the fabricated profiles were measured; the profiles were examined under a microscope to identify and study their cracking; and the mechanical properties of the pultruded composite were determined. The spring-in was measured immediately after fabrication and then at intervals of two to three days over a 90-day period. The spring-in angle was found to increase with increments in the pulling speed. The profiles produced at the lower pulling speeds (200 and 400 mm/min) exhibited no significant differences in matrix cracking or mechanical characteristics. By comparison, at the high pulling speed (600 mm/min), wherein a large part of the profile is polymerized after exiting the die, the formation of delamination perpendicular to the matrix cracks was observed. Furthermore, at this pulling speed, there were increased variations in the strength and Young's modulus values and decreased interlaminar shear strength.